KARAKTERISTIK BAHASA GURU DALAM INTERAKSI BELAJAR MENGAJAR BAHASA INDONESIA DI KELAS XII MIPA 2 SMAN 1 BANGIL KABUPATEN PASURUAN - Mirna, Wa (LP2M IAIN Ambon, 2019)
Abstract The purpose of this study is to describe the language characteristics of teachers in learning activities at SMAN 1 Bangil, Pasuruan Regency. Research data in the form of teacher's speech containing the characteristics of the teacher's language in the form of repetition, simplification, question sentences, code mixing, and code switching. The results showed the characteristics of the teacher's language in the teacher's speech during learning activities. Repetition is contained in the teacher's speech at SMAN 1 Bangil in class XII MIPA 2 when explaining, asking, ordering and strengthening. Simplification is in the speech at SMAN 1 Bangil in class XII MIPA 2 when asking questions and commanding. The question sentence is contained in the teacher's speech at SMAN 1 Bangil in class XII MIPA 2 when explaining, commanding, and asking questions. The code mix is contained in the teacher's speech at SMAN 1 Bangil in class XII MIPA 2 when explaining, asking, and reinforcing. The code switching is found in the teacher's activities at SMAN 1 Bangil in class XII MIPA 2 when asking questions, commanding, and strengthening. Keywords: teacher language, teacher language characteristics, learning activities Abstrak Tujuan penelitian ini adalah mendeskripsikan karakteristik bahasa guru dalam kegiatan pembelajaran di SMAN 1 Bangil Kabupaten Pasuruan. Data penelitian berupa tuturan guru yang mengandung karakteristik bahasa guru berupa repetisi, penyederhanaan, kalimat tanya, campur kode, dan alih kode. Hasil penelitian menunjukkan adanya karakteristik bahasa guru pada tuturan guru saat kegiatan pembelajaran. Repetisi terdapat dalam tuturan guru di SMAN 1 Bangil di kelas XII MIPA 2 saat menjelaskan, bertanya, memerintah dan menguatkan. Penyederhanaan terdapat dalam tuturan di SMAN 1 Bangil di kelas XII MIPA 2 saat bertanya dan memerintah. Kalimat Tanya terdapat dalam tuturan guru di SMAN 1 Bangil di kelas XII MIPA 2 saat menjelaskan, memerintah, dan bertanya. Campur kode terdapat dalam tuturan guru di SMAN 1 Bangil di kelas XII MIPA 2 saat menjelaskan, bertanya, dan menguatkan. Alih kode terdapat dalam kegiatan guru di SMAN 1 Bangil di kelas XII MIPA 2 saat bertanya, memerintah, dan menguatkan. Kata kunci: Bahasa guru, karaketeristik bahasa guru, kegiatan pembelajaran